Development of Encapsulated Self Healed Microparticles: Evaluation by RSM - Yadava, Sunil; Naik, Jitendra; Patil, Jayesh; Mokale, Vinod (Micro and Nanosystems, 2016)
Background: Present work deals with the development of a hydrophilic drug encapsulated self healed microparticles. Objective: To develop encapsulated microparticles of Ciprofloxacin, model hydrophilic drug. Method: A modified o/o/w multi emulsion solvent evaporation method was used for the development of Ciprofloxacin encapsulated microparticles. Aluminium hydroxide was used as a healing agent. This method produced encapsulated carrier for hydrophilic drug and sustained release system. Microparticles were evaluated by using 3-level factorial design. Results: The obtained encapsulated microparticles were characterized by FTIR, FESEM and elemental analysis. The variables such as plymer (X1) and aluminium hydroxide (X2) were optimized for the maximum encapsulation efficiency (Y1) and the optimum drug release (Y2) with the help of the response surface methodology (RSM). The RSM predicted that, both X1 and X2 were significant for the Y1 (pvalues- 0.0006 & 0.0023) and Y2 (p- values-0.0003 & <0.0001). An increase in the concentrations of the polymer and aluminium hydroxide increased Y1 and decreased Y2. The obtained optimum value of Y1 and Y2 were 80.86 and 55.34, respectively. Those were well in agreement with the predicted value by RSM. In- vitro drug release study was also performed and data were checked for various kinetic models to confirm the sustained release behaviour of the microparticles. Conclusion: The results showed that concentration of ethylcellulose and aluminium hydroxide greatly influenced the % encapsulation efficiency and drug release. The absence of drug polymer interactions was confirmed by FTIR spectroscopy. In-vitro drug release analysis and its kinetic modelling confirmed the sustained release behaviour of the microparticles.
Keywords: encapsulation